Case report: Diagnosis of NUT carcinoma of hepatic origin by next-generation sequencing - Ardalan, Bach; Azqueta, Jose; Luo, Jia; French, Christopher (Frontiers in Oncology, 2024)
NUT carcinoma is a rare subcategory of squamous cell carcinoma. The latter is primarily characterized by the fusion of the coding sequence NUTM1 on chromosome 15q14 with BRD4 or BRD3, both of which are acetyl-histone binding bromodomains. This tumor is often misdiagnosed due to its rarity and its histological similarity with other squamous cell carcinomas. It typically presents as a poorly differentiated squamous cell carcinoma in the head, neck, and mediastinal region, and has no distinct clinical characteristics that set it apart from other malignancies. Although uncommon, other NUT carcinomas have been reported in the literature outside of the midline region. Through next-generation sequencing, we were able to correctly diagnose our patient with the first-documented case of NUT carcinoma of hepatic-only origin.